2011
DOI: 10.1177/1359105311410513
|View full text |Cite
|
Sign up to set email alerts
|

Do Parents Maintain or Exacerbate Pediatric Functional Abdominal Pain? A Systematic Review and Meta-analysis

Abstract: Parents may maintain or exacerbate functional abdominal pain (FAP) in children through modeling of physical symptoms and solicitous responses to the child's complaints. This systematic review and meta-analysis aimed to examine these relationships. Parents of children with FAP reported more physical symptoms than parents of healthy children (effect size d = .36). As all studies were cross-sectional or retrospective, the causal direction was unclear. For parental responses to child complaints, not enough studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…55 Although parent responses to child pain are often emphasized in family-based interventions and considered a key factor in the development and maintenance of pediatric chronic pain, 27 a systematic review of parent behavioral responses to pediatric abdominal pain found little evidence to support these assertions. 51 Two studies have evaluated the longitudinal trajectory of parent responses to child pain in the context of randomized, controlled trials of cognitive-behavioral therapy for pediatric chronic pain. 26,27 Although both studies found decreases in parents, maladaptive behavioral responses to child pain in response to cognitive-behavioral therapy, these decreases did not correspond with significant decreases in children’s self-reported pain 27 or disability.…”
Section: Discussionmentioning
confidence: 99%
“…55 Although parent responses to child pain are often emphasized in family-based interventions and considered a key factor in the development and maintenance of pediatric chronic pain, 27 a systematic review of parent behavioral responses to pediatric abdominal pain found little evidence to support these assertions. 51 Two studies have evaluated the longitudinal trajectory of parent responses to child pain in the context of randomized, controlled trials of cognitive-behavioral therapy for pediatric chronic pain. 26,27 Although both studies found decreases in parents, maladaptive behavioral responses to child pain in response to cognitive-behavioral therapy, these decreases did not correspond with significant decreases in children’s self-reported pain 27 or disability.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, chronic pain in both parents was associated with significantly poorer health in children than having one or neither parent with chronic pain 35 . Extensive literature suggests that using the social learning theory 34,36,37 and the social communication model of pain 38 parents can influence their children's perception of pain by modelling their pain behaviour and reinforcing their children's pain complaints with solicitous responses 39 -children express their pain in the same way as their parents behave with pain.…”
Section: Risk Factorsmentioning
confidence: 99%
“…The lack of empirical research in this area is particularly concerning, as chronic pain conditions are highly prevalent (approximately 20–25% of youth) and can be disabling 15,16 . Although an abundance of research has examined the role of various psychosocial factors in youth with chronic pain that may be proxies for ACEs, including psychological comorbidities 1719 , parenting factors 20,21 , and social functioning 22 , targeted research on the relationship between chronic pain and ACEs in children remains limited, since exposure to ACEs is rarely assessed in a systematic way in the context of clinical care or research. However, preliminary evidence is compelling with recent research indicating that youth with a history of ACEs such as abuse are 21% more likely to hold the diagnosis of a chronic medical condition including a chronic pain condition (e.g., migraines, rheumatic disease) than their same-aged peers with no ACE history 2 .…”
Section: Aces In Chronic Painmentioning
confidence: 99%